'N OORSIG VAN DIE SALT-OOREENKOMSTE - Van Loggerenberg, J.P.B (Scientia Militaria - South African Journal of Military Studies, 2012)
The writer summarises the progress of the SALT negotiations to date and assesses their impli.cations. Before the SALT I negotiations, the United States was well in the lead in the development of anti ballistic systems, but lapsed into a sense of false security when it was seen that the Soviet Union was willing to negotiate. While the United States made cuts in expenditureand research, the Soviet Union, ignoring preliminary SALT agreements, went a long way towards making up the leeway. When the two sides signed the SALT Interim Agreement it appeared thatthe long.term advantage might lie with the Soviet Union, even though the United States was stillin the stronger position at the time. Whether the Soviet Union had gained a concrete advantagewill depend on the outcome of the Salt II negotiations. The writer points out that, while the Soviet Union has not denied its basic aim of world domination, the SALT negotiations are possibly being used to further this aim - a factor which he feels the West is overlooking.